Graphic Design and Print Production Fundamentals - Collins, Wayne; Haas, Alex; Jeffery, Ken; Martin, Alan; Medeiros, Roberto; Tomljanovic, Steven (Open textbook library., 2015)
This textbook -- written by a group of select experts with a focus on different aspects of the design process, from creation to production -- addresses the many steps of creating and then producing physical, printed, or other imaged products that people interact with on a daily basis. It covers the concept that, while most modern graphic design is created on computers using design software, the ideas and concepts don't stay on the computer. The ideas need to be completed in the computer software, then progress to an imaging (traditionally referred to as printing) process. Keywords are highlighted throughout and summarized in a Glossary at the end of the book, and each chapter includes exercises and suggested readings.